Patterns of improvement in functional ability and predictors of responders to dual-task exercise: A latent class analysis - Ho, Vanda; Chan, Yiong Huak; Merchant, Reshma Aziz (Frontiers in Public Health, 2023)
Background Exercise is the pillar for healthy aging. “Non-responders” may be due to a mismatch in exercise prescription. A latent cluster analysis (LCA) profile can be useful to uncover subpopulations sharing similar profiles or outcomes. We aim to use the LCA to develop a response prediction model for older adults who would benefit from The Healthy Aging Promotion Program for You, a community-embedded dual-task exercise program. Methods A total of 197 participants completed the 3-month follow-up, and the complete data were available for 136 community-dwelling older adults. Inclusion criteria were age ≥60 years, pre-frail or frail and ambulant, mild cognitive impairment, and ability to provide consent. Data collected include demographics, education, falls, physical function (Katz ADL scale and Lawton's IADL scale), physical activity (rapid assessment of physical activity), cognition (Montreal Cognitive Assessment; MoCA), frailty (FRAIL scale), and perceived health, pain, anxiety/depression, fear of falling, and social isolation (Lubben Social Network Scale). The body mass index (BMI), handgrip strength, and short physical performance battery (SPPB) were measured. Those who improved in frailty, anxiety/depression, pain, Lubben, MoCA, SPPB, fear-of-falling, physical activity, falls, and HGS were classified as responders. Results The mean age was 74.7 years, BMI 23.5 kg/m2, 23.5% were male, 96.3% were of Chinese ethnicity, 61% were pre-frail, education level of 4.3 years, and the MoCA score of 23.3 ± 4.8. Two clusters were identified: non-responders (61.8%) and responders (38.2%). Responders had significant improvement in cognition (44.2% vs. 0, p < 0.001) and SPPB (gait:28.8% vs. 0, p < 0.001; balance:42.3% vs. 15.5%, p = 0.001; chair-stand:65.4% vs. 4.8%, p < 0.001). Responders were significantly older (76.9 vs. 73.3 years, p = 0.005), had higher BMI (24.8 vs. 22.8 kg/m2, p = 0.007), lower education (3.4 vs. 4.9 years, p = 0.021), lower MoCA scores (21.8 vs. 24.3, p = 0.002), and lower SPPB scores (8.7 vs. 10.6, p < 0.001). The predictive variables for the responder cluster were age ≥75 years, BMI ≥23 kg/m2, robust, no anxiety, pain, fear of falling, MoCA ≤22, Lubben ≤12, SPPB score: chair-stand ≤2, balance ≤2, gait >2, handgrip strength <20 kg, no falls and RAPA >3. With an optimal cut-off of ≥12, this prediction model had sensitivity of 76.9%, specificity of 70.2%, positive predictive value 61.5%, and negative predictive value of 83.1%. Conclusion Response to dual-task exercise was influenced by age, SPPB, BMI, and cognition. Prospective longitudinal studies are needed to validate this LCA model and guide the development of public health strategies.